2014
DOI: 10.2478/s11536-013-0192-3
|View full text |Cite
|
Sign up to set email alerts
|

Differences on the prevalence of cervical HPV between Lithuania and Belarus

Abstract: AbstractIn some countries the cervical cancer incidence and mortality rates are much higher compared to the European average. The differences of HPV and its type prevalence between countries and regions influence cervical cancer incidence and mortality. Regarding the differences in cervical cancer incidence and mortality in Lithuania and Belarus, the aim of this study was to describe HPV infection level and HPVs type distribution among two study groups of patients with moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…HPV 16 was the most prevalent subtype, detected in 50% of cervical cancers and CIN 2/3 cases, followed by ~ 10% prevalence of HPV 18 and HPV 33 in both disease groups. [22] Estonian data is closely mirroring these results -with prevalence of 55%, 12% and 8% for HPV 16, 33 and 31 respectively among women with high grade cervical lesions. [23] According to the study from Latvia by Silins et al (2004), the most common HPV DNA type found in cervical samples of the cervical cancer patients was HPV 16 (60.6%), followed by HPV 18 (9.0%), HPV 31 (5.4%), HPV 45 (3.2%), and HPV33 (2.7%).…”
Section: ) [18]supporting
confidence: 52%
“…HPV 16 was the most prevalent subtype, detected in 50% of cervical cancers and CIN 2/3 cases, followed by ~ 10% prevalence of HPV 18 and HPV 33 in both disease groups. [22] Estonian data is closely mirroring these results -with prevalence of 55%, 12% and 8% for HPV 16, 33 and 31 respectively among women with high grade cervical lesions. [23] According to the study from Latvia by Silins et al (2004), the most common HPV DNA type found in cervical samples of the cervical cancer patients was HPV 16 (60.6%), followed by HPV 18 (9.0%), HPV 31 (5.4%), HPV 45 (3.2%), and HPV33 (2.7%).…”
Section: ) [18]supporting
confidence: 52%
“…In Lithuania, 74.2% women with CIN2/3 and 85.6% of women with cervical cancer, were hrHPV positive. HPV 16 was the most prevalent subtype, detected in 50% of cervical cancers and CIN 2/3 cases, followed by ~ 10% prevalence of HPV 18 and HPV 33 in both disease groups [22]. Estonian data is closely mirroring these resultswith prevalence of 55%, 12% and 8% for HPV 16, 33 and 31 respectively among women with high grade cervical lesions [23].…”
Section: Hpv In Cervical Precancerous Lesions and Cervical Cancermentioning
confidence: 79%